Comparative Study of Proximate, Fatty and Amino Acids Composition of Wild and Farm-Raised African Catfish Clarias gariepinus in Kaduna, Nigeria - Ibhadon, S.; Abdulsalami, M.S.; Emere, M.C.; Yilwa, V. (Pakistan Journal of Nutrition, 2014)
Proximate, fatty and amino acids composition of wild and farm-raised African catfish Clarias gariepinus from River Kaduna and Fadama fish pond (NAF base, Kawo) in Kaduna were evaluated. Juvenile and matured fishes from the two existing environment were investigated to ascertain differences in body composition of the fishes. The range of proximate composition were; moisture content 69.3-79.3%, crude protein 10.40-11.43, lipid content 1.15-2.08 and ash content 1.02-1.22%. Variation in percentage composition exist among individuals but there was however no significant differences(p>0.05) in the mean body composition of the fish. A total of seven major fatty acids, seven trace metals and seventeen amino acids was found in the fish. Linoleic acid a polyunsaturated fatty acids which cannot be synthesized by humans was found in wild catfish while the matured catfish had a higher amount of unsaturated fatty acids. Farm-raised cat fishes had a higher amount of total amino acids while histidine and cysteine were low in both wild and farm-raised catfish samples. This study showed that wild and farm-raised catfish is beneficial to health and that water quality should be maintained.